Design and Development of A Web-Based Internet Complaint Information System using A Rule-Based Method at PT Integra Kreasitama Solusindo - Fakhriyah, Mardhiyah; Kurniawan, Rakhmat (IJISTECH (International Journal of Information System and Technology), 2024)
This study focuses on the development of an information system specifically designed to address issues related to service disruption complaints frequently encountered by customers of PT Integra Kreasitama Solusindo. In an era marked by significant advancements in information technology, it is imperative for service companies to ensure that their customers can easily and efficiently report any disruptions they experience. This research includes comprehensive system design steps, encompassing the creation of an intuitive user interface, the development of a well-structured database, and the modeling of the overall system workflow. The primary objective of the developed information system is to facilitate the reporting of complaints, allow customers to monitor the progress of their complaints, and enable the support team to provide prompt and relevant responses. A rigorous testing methodology was employed during the development phase to ensure the system's performance and reliability. Evaluation results demonstrate that the system significantly optimizes the efficiency of managing service disruption complaints, resulting in faster response times. Additionally, the system enhances the overall management of customer service. This research underscores the importance of leveraging information technology to improve customer service quality, thereby positioning PT Integra Kreasitama Solusindo as a competitive entity in the digital era. The findings of this research are expected to offer valuable insights for other companies facing similar challenges in managing customer complaints